2015
DOI: 10.1111/acer.12707
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking During Adolescence Disrupts Se Homeostasis and Its Main Hepatic Selenoprotein Expression

Abstract: Due to the above, and to find whether a Se supplementation therapy improves these situations, it would be interesting to explore in more depth the relationship between Se, the high oxidation found, and the depressed immune response reported in BD adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, BD rats presented high ALT and AST serum values; this increase in transaminases indicates that hepatic damage is taking place [ 35 ]. The same results of transaminases and hepatic damage are described in clinical trials in adolescents exposed to intensive alcohol consumption [ 36 ] and in experimental BD-exposed animals [ 37 , 38 ]. When FA is supplemented, these values decrease, particularly ALT values.…”
Section: Discussionmentioning
confidence: 59%
“…However, BD rats presented high ALT and AST serum values; this increase in transaminases indicates that hepatic damage is taking place [ 35 ]. The same results of transaminases and hepatic damage are described in clinical trials in adolescents exposed to intensive alcohol consumption [ 36 ] and in experimental BD-exposed animals [ 37 , 38 ]. When FA is supplemented, these values decrease, particularly ALT values.…”
Section: Discussionmentioning
confidence: 59%
“…Clinical and research studies have demonstrated that acute or chronic alcohol consumption alters Se bioavailability and its antioxidant function by affecting selenoprotein tissue expressions [ 146 , 147 ]. Nonetheless, few studies analyze Se homeostasis during pregnancy after EtOH exposure [ 148 ] in the mother or fetus; however, an impairment of the selenoprotein GPx in FASD during the embryonic period in different tissues is well described [ 149 , 150 , 151 , 152 , 153 ].…”
Section: Oxidative Stress-programming Pathologies and Sementioning
confidence: 99%
“…From a nutritional point of view, neither BD nor Se supplementation affects Kcal intake or body weight. With regard to liver, previous research in this laboratory has described hepatic damage associated to BD exposition during adolescence 37,41,42 . Moreover, this lab has previously described that Se plays an important role in the liver of BD exposed animals, since BD deeply affects hepatic selenoprotein expression; and when selenite is supplied, hepatic selenoproteins expression increased, leading to a better oxidative, inflammatory and apoptotic liver profile 3 .…”
Section: Nutritional and Hepatic Parametersmentioning
confidence: 99%